Putting at risk what we know: Reflecting on the drug-using subject in harm reduction and its political implications - Moore, David; Fraser, S. (ELSEVIER, 2006)
This paper provides a poststructuralist analysis of the cultural inscription of drug-using subjects in the neo-liberal discourses of contemporary harm reduction. We argue that although neo-liberal discourses downplay material constraints on individual human agency, divert policy and practice away from structural issues, limit the conception of effective strategies for harm reduction and ignore alternative formulations of the subject, they are also potentially empowering for drug users. Approximating the neo-liberal subject offers political benefits in terms of recognition, trust and legitimation, even as those values assume and reproduce understandings of behaviour, thought and sociality that fit only poorly the realities faced by many drug users. We explore this dilemma and consider three available directions in formulating the subject of harm reduction: (1) embracing the neo-liberal subject; (2) employing a more contextualised version of the neo-liberal subject; and (3) adopting alternative notions of subjectivity, extending the critique of the neo-liberal subject to all citizens, not solely drug users. To clarify some of these issues surrounding this strategic process, the paper considers another field in which struggles over the nature of the subject have been conducted—feminism. The intention is not to resolve the question of the most appropriate subject for harm reduction, but to sketch the political consequences of adopting particular models of the subject as a stimulus to further discussion and debate.